Word Tasting: towards a sensorial experience of language and thought in the actor’s work - Holesgrove (Universidade de São Paulo – USP, São Paulo/SP, Brazil), Thomas William (Revista Brasileira de Estudos da Presença, 2022)
Starting from the metaphorical conception, the word is nutrient, we propose a series of four exercises as a word tasting to investigate the sensory aspects of language and thought in the actor’s work. Through an exploration of the proximity between speaking and eating, the exercises seek to stimulate awareness of the way in which words reverberate through the entire body. The proposal aims to reduce the mechanical control of organic processes and the direct manipulation of the voice in accordance with preconceived esthetic notions. At the same time, it proposes to provoke a deeper physical-intellectual-emotional-sociocultural experience of the text in the theatre.